Morphometric and genetic differentiation among populations of flat‐headed cusimanse (Crossarchus platycephalus) in Nigeria. Issue 14 (25th June 2018) - Oguntuase, Bukola G.; Ogunjemite, Babafemi G.; Meisel, Richard P.
Abstract: Geographic barriers can partition genetic diversity among populations and drive evolutionary divergence between populations, promoting the speciation process and affecting conservation goals. We integrated morphological and genomic data to assess the distribution of variation in the flat‐headed cusimanse ( Crossarchus platycephalus ), a species of least conservation concern, on either side of the River Niger in Nigeria. Ecological disturbances affect the conservation status of many other animals in this region. The two populations were differentiated in the snout and fore limbs, with greater morphological diversity in the western population. We used Restriction site Associated DNA sequencing (RAD‐seq) and identified two genotypic clusters in a STRUCTURE analysis. Individuals from the eastern population are almost entirely assigned to one cluster, whereas genotypes from the western population are a mixture of the two clusters. The population from west of the River Niger also had higher heterozygosity. The morphological and population genetic data are therefore in agreement that the population from west of the River Niger is more diverse than the eastern population, and the eastern population contains a subset of the genetic variation found in the western population. Our results demonstrate that combining morphological and genotypic measures of diversity can provide a congruent picture of the distribution of intraspecific variation. The results also suggest that future work should explore the role of the River Niger as a natural barrier to migration in Nigeria. Abstract : Population genomic and morphological data were combined to demonstrate that populations of a dwarf mongoose on either side of the River Niger are differentiated from each other. The molecular and phenotypic data are in agreement that a population to the west of the river is more diverse than an eastern population. These results demonstrate the utility of combining molecular and morphological data in surveys of intra‐species diversity.